Pengaruh Penerapan E-filing SPT Tahunan Orang Pribadi Terhadap Kepatuhan Pelaporan SPT dan Efektivitasnya di KPP Pratama Salatiga: Studi Kasus Tahun 2019-2022 - Saktiko, Ananta; Abdullah, Muhammad Al Faruq (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the effect of implementing e-filing of Individual Annual SPT on SPT reporting compliance and its effectiveness at KPP Pratama Salatiga in the 2019-2022 period. The method used is quantitative with multiple linear regression analysis. The results of the research show that the implementation of e-filing does not have a significant effect on reporting compliance with Individual Annual Tax Returns with a significance value of 0.160 (p 0.05). However, there is a significant influence of the implementation of e-filing on the effectiveness of Annual SPT reporting with a significance value of 0.049 (p 0.05). ANOVA analysis shows that together, compliance (X1) and effectiveness (X2) do not have a significant influence on Annual SPT reporting (Y), with a significance value of 0.067 (p 0.05) and F count of 2.989 which is smaller than F table 3.32. The coefficient of determination shows that compliance and effectiveness together only contribute 18.1% to Annual SPT reporting, while 81.9% is influenced by other factors. However, the compliance and effectiveness variables together have a positive influence with a correlation value of r of 0.426, which is in the sufficient category (0.40-0.599). In conclusion, the implementation of e-filing is effective in increasing the efficiency of SPT reporting, but does not significantly affect taxpayer compliance in reporting their Annual SPT. This research provides insight for KPP Pratama Salatiga to continue to improve e-filing socialization and consider other factors that influence Annual SPT reporting compliance.